Choice of Structure, Business Model and Portfolio: Organizational Models of Knowledge Transfer Offices in British Universities. (19th March 2017) - Sengupta, Abhijit; Ray, Amit S.
Abstract: This paper addresses the gap in the knowledge transfer literature around how universities choose specific organizational models for their knowledge transfer offices (KTOs). Organization theory points towards strong interlinkages between strategy, structure and processes in organizations. This motivates an exploration of similar links within the organizational setup of KTOs. In doing so, the paper provides a unified theoretical framework around a university's choice of structure, business model and strategic preferences for their KTOs linked to university‐specific contextual factors. A qualitative approach is used wherein four very distinct British universities are examined as individual case studies. The authors find that strategic aims of the university around practitioner engagement, the quantity of applied research and research specialization are key factors in determining the organizational characteristics of the KTO. The theoretical framework derived from the cases makes two key contributions to the university knowledge transfer literature. First, it links the university‐level contextual factors to the local model of knowledge transfer. Second, it allows us to develop a set of generic models of knowledge transfer, which can potentially guide universities to develop their own specific models.